Educational attainment: Success to the successful - Peter John Anthony; David Gould; Gina Smith (Laureate Education Inc, 2013)
Systems archetypes are patterns of structure found in systems that are helpful in understanding some of the dynamics within them. The intent of this study was to examine educational attainment data using the success-to-the-successful archetype as a model to see if it helps to explain the inequality observed in the data. Data covering 1990 to 2009 was collected from the United States Census Bureau for the United States, as well as for the States of Georgia and Washington. Findings indicated that this archetype is useful in explaining the variation, and there are several other terms and concepts that are helpful as well as the terms / concepts: success-to-the successful, the rich get richer, Pareto's law, Zipf's law, and power law distributions are related and sometimes used interchangeably. DOI: 10.18870/hlrc.v3i1.98